Automatic Lecture Meeting Folder Based on Hierarchical Directories - Wisnu Yudo Untoro (Universitas Islam Sultan Agung, 2020)
The lecture meeting is a face-to-face meeting between a teacher and the learners in the classroom in the implementation. In the rules that apply that every lecture meeting a teacher must put the signature on the sheet of paper attendance in the signature column. Checking the lecture meeting in this way has its weaknesses, namely easily manipulated. For this reason, there is an idea to design a system that can make automatic college meeting folders every time the teacher runs this system. The experimental results show that the system can automatically create lecture meeting folders for various subject names that are already available.